The Death of Everyone: Robert Lifton, Christian Theology and Apocalyptic Imagery - Bregman, Lucy (Horizons, 1986)
This paper explores an issue raised by psychologist Robert Lifton in The Broken Connection. Lifton believes the present threat of total extinction through nuclear war has drastically affected humanity's ability to reconnect life and death, and to make individual death meaningful. The death of everyone—as an imaginable possibility—defeats all expressions of "symbolic immortality," affirmations of continuity and hope.How has Christian theology met this predicament? Twentieth-century history has been so menacing and overwhelming that some theologians have found in apocalyptic-eschatological imagery the most appropriate framework to encounter that history and discern its spiritual meaning. Yet this imagery, even when de-literalized, provides at best ambiguous answers. Early twentieth-century theology—Schweitzer, Case—recognized the importance of apocalyptic thought for the New Testament, but easily repudiated this for contemporary life. In contrast, later thinkers such as Cullman, Brunner, and Moltmann make extensive use of eschatological imagery. However, they face the problem raised by Lifton: how to make "hope" vivid to readers already gripped by a future of possible universal catastrophe.